HUBUNGAN KEJADIAN ANEMIA DENGAN JUMLAH PERDARAHAN MENSTRUASI DAN NYERI MENSTRUASI PADA REMAJA PUTRI (DI SMK ABDI NEGARA TUBAN - Devira Aulia Rahma; Nur Maziyah Hurin'in (Rena Cipta Mandiri, 2025)
Anemia among adolescent girls is a health problem with a high prevalence. Excessive menstruation and dysmenorrhea are suspected to contribute to the occurrence of anemia. This study aimed to analyze the relationship between anemia incidence, menstrual blood loss, and menstrual pain among adolescent girls at SMK Abdi Negara Tuban. This study used a cross-sectional design involving 37 respondents selected through simple random sampling. Data were collected using the PBAC to measure menstrual blood loss, the VAS to assess pain intensity, and the EasyTouch GCHb to measure hemoglobin levels. Data were analyzed using the Spearman test. The results showed a significant relationship between menstrual blood loss and anemia (r=0.563; p=0.000), as well as between menstrual pain and anemia (r=0.708; p=0.000). It can be concluded that the greater the menstrual blood loss and pain intensity, the higher the risk of anemia. Reproductive health education, iron supplementation, and monitoring of the nutritional status of adolescent girls are recommended.